(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Gavrilenko K. Management of monitoring learning achievements of students of pedagogical universities. The features of management of educational achievements of students of pedagogical institutions of higher learning monitoring are considered. Essence of concepts «monitoring» and «monitoring is exposed in education».